Development of rectangular rubber isolators for a tunnel-form structure subjected to seismic excitations - Altalabani, Diyar Nasih Qader (2021)
The tunnel-form building system is gaining popularity due to its characteristics in time saving in construction. However, the tunnel-form structure is more vulnerable against lateral loads because of its large weight to stiffness ratio, which can potentially intensify the forces induced to the structure during seismic events. To improve this vulnerability during earthquake hazards, seismic base isolation systems can be incorporated into the tunnel-form structure. Among others, rubber isolators have been adopted extensively as effective base isolation systems for various building and bridge structures around the world. However, the most common shapes used for base isolators are circular and square, as the anisotropic isolation system has typically been designed by employing symmetrical-shaped seismic isolators. While, these configurations are not applicable for the tunnel-form building system, since the distribution of the loads corresponding to the shear wall does not provide a uniform support condition along the walls. Therefore, an attempt was made in this study to develop rectangular rubber isolators with couple cores that are applicable for tunnel-form structures. A rectangular isolator with dual lead cores instead of a single core is proposed to enhance the efficiency of the isolator along the direction of the wall in terms of lateral shear resistance and energy absorption capacity. Previous studies had revealed the poisoning effects of lead material exposure on the environment and human health. Thus, to avoid adverse effects caused by exposure to lead material, a rectangular isolator with dual rubber cores instead of lead cores was developed. In this study, the rubber cores in a rectangular isolator are confined with a single layer of CFRP wrap and stainless steel tube to improve the lateral shear behavior and damping ratio of the isolators. For the sake of comparison, a rectangular rubber isolator without cores is also considered in this study. Five full-scale rectangular isolators are manufactured and experimentally tested under a vertical compressive load and horizontal displacements to derive and evaluate their hysteresis response. Finite element models for the 5 mentioned large-scale isolators are developed, and their performance under cyclic loads is investigated. The experimental and numerical results were then compared and they showed a good agreement. Based on the experimental testing and simulation results, the CFRP and stainless-steel tube confinement were found effective in improving the behavior of rectangular isolators with rubber cores in terms of damping ratio and energy dissipation capacity. Furthermore, the proposed rectangular isolators are implemented into a 5-story tunnel-form structure, and nonlinear dynamic analyses were conducted for different structural performance levels. The seismic performance of the fixed base and base-isolated buildings is investigated by performing the Incremental Dynamic Analysis (IDA) using a suite of 10 pairs of earthquake ground motion records. Also, the fragility curves were created based upon the results of incremental dynamic analysis as it is one of the effective methods of conducting nonlinear dynamic analyses to gather data to estimate the fragility curves. In all models, the results showed that the probabilities of exceeding the Immediate Occupancy (I.O) performance level for coupling beams under both DBE and MCE hazard levels are less than 10 and 20%, respectively. This way, under both DBE and MCE hazard scenarios, these values for the walls are about 3 and less than 6%, respectively. It can be concluded that the tunnel-form structure can practically satisfy the Immediate Occupancy (I.O) performance level by implementing the proposed rectangular isolator systems even under severe seismic excitations. Finally, the finite element parametric study based on the validated finite element models is conducted on 12 rectangular rubber isolators with one, two, and four square lead and rubber cores subjected to lateral cyclic loads. As in the case of prototype samples, the square rubber cores are confined with CFRP and steel layers which play a vital role, as concluded earlier, in improving the damping parameter of the proposed rectangular isolators. The numerical parametric study results showed a slight increase in the damping ratio with increasing the number of rubber cores. The results also indicated no remarkable difference between isolators tested along the length and those tested along the width. This shows that the response of the isolator does not depend on its shape rather than it is dependent on the amount and number of lead/rubber cores.